Kajian Potensi Dan Peluang Investasi Pengelolaan Limbah Bahan Berbahaya Dan Beracun (B3) Medis Di Kota Surakarta - Tri Wisnu Dono Kuncoro; Fitria Indrati; Rony Widjanarko; Rouf Adima (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
Hazardous Toxic Waste (B3) is a challenge as well as the latest threat to the people of Indonesia. The management of B3 waste, especially medical B3 waste, needs serious attention given that the production of medical B3 waste continues to increase from year to year. The potential for medical hazardous and toxic waste generated in Surakarta City is quite large, originating from Health Service Facilities which include 19 Hospitals, 17 Health Centers, 1 DKK Lab, 12 Health Laboratories, 102 Main and Primary Clinics, 1,399 Independent Practicing Doctors, 251 Independent Practicing Dentists , 7 Independent Practice Midwives, Beauty Clinic and 6 Veterinary Clinics. The urgency of building a B3 waste treatment plant is the limited B3 waste treatment facilities which can threaten the environment and the potential for regional income.